The Role of the Midwife in Fulfilling the Reproductive Rights of Adolescents at the Dlingo 1 Health Center, Bantul - Lestari, Reni Tri; Fitriana, Yuni (Soepra Jurnal Hukum Kesehatan, 2023)
Midwives play an important role in providing adolescent reproductive rights. The role of midwives in reproductive health services is contained in Regulation of the Minister of Health Number 28 of 2017 concerning Permits and Implementation of Midwife Practices. Based on the law of the Republic of Indonesia number 35 of 2014 and the regulation of the Minister of Health number 25 of 2014, teenagers are those aged 10-24 years old and are not married. Based on the biological condition of adolescents, the minimum age for marriage is 21 years for women and 25 years for men. At this age, the reproductive organs have reached maturity and reproductive. Early marriage has the risk of increasing the Maternal Mortality Rate (MMR) and in certain cases causing Low Birth Weight (LBW). Dlingo District in Bantul Regency had the highest early marriage rate. Early marriages in Dlingo are dominated by couples aged 13-14 years. This study aims to identify and analyze the role of midwives in fulfilling adolescent reproductive health rights. This is a sociological juridical research that discusses the juridical and social aspects surrounding certain legal phenomena of empirical juridical. This is an analytical descriptive research that presents observational data without testing hypotheses.The results showed that midwives have not played a maximum role in fulfilling adolescent reproductive rights. It was caused by juridical factors and health worker factors, especially midwives.